PROFITABILITY DRIVERS: AN IN-DEPTH ANALYSIS OF HEALTH INDUSTRY COMPANIES - Faizul Mubarok; Muhammad Irfan Kurnia; Laila Mutiara; Yoga Dwi Prakoso (Universitas Muhammadiyah Tangerang, 2025)
This research examines the influence of liquidity, activity, interest rate, and firm value variables on the profitability of healthcare companies listed on the Indonesia Stock Exchange. Employing purposive sampling, the study chose eight healthcare companies as its sample from 2018 to 2022. Data analysis was carried out by applying a fixed effect model. The results showed that two variables, namely asset turnover (activity ratio) and interest rates, have a significant influence on the profitability of companies in the healthcare sector. However, the variables of current ratio (liquidity) and firm value have yet to be proven to influence the level of profitability of these companies significantly. This finding implies that managers of companies in the healthcare sector need to pay attention to these factors in managing finances and increasing profitability. Improving efficiency in asset utilization and a better understanding of interest rate conditions can be effective strategies. Meanwhile, liquidity and firm value do not significantly impact profitability, which may provide additional insights for managerial decision-making in this sector.